Pengembangan E book Audio Visual Cerita Rakyat Asal Usul Pantai Papuma Jember pada Pembelajaran Tema 2 Subtema 1 Manfaat Tumbuhan Bagi Kehidupan Manusia untuk Peserta Didik Kelas III - Dillon Justitia Suprapto (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Technological developments which are currently increasingly rapid require all levels of society to keep up with the times, one of which is teachers. The availability of facilities is not balanced with the teacher's ability to use technology, making classroom learning tend to be boring which affects students' learning motivation. The aim of this research is to examine how to develop an audio-visual e-book of folklore from the origins of Jember's Papuma Beach on theme 2 sub-theme 1 for class III students that is valid, effective and practical. It is hoped that the easy creation and use of e-books will help teachers create learning media and increase student learning motivation. The research method used is development research. The research used 27 class III students, after carrying out learning using e-books it was discovered how to make e-books using the flipbook application and showed that audio-visual e-books had a validity level of 89.12 (very valid), an effectiveness level of 89% ( effective), and a level of practicality of 92.25 (very practical). It can be concluded that the audio visual e book of folklore from the origins of Jember's Papuma Beach which is applied to learning theme 2 subema 1 for class III B at SDN Kepatihan 06 Jember is said to be valid, effective and practical.
Reaploud Repository February_Hasyim
Keywords: e-book Development; Folklore E-books; The Influence Of E-books On Learning Outcomes